Commercial thorium fuel manufacture and irradiation: Testing (Th, Pu)O2 and (Th, U)O2 in the "Seven-Thirty" program. (January 2015) - Insulander Björk, Klara; Drera, Saleem S.; Kelly, Julian F.; Vitanza, Carlo; Helsengreen, Christian; Tverberg, Terje; Sobieska, Matylda; Oberländer, Barbara C.; Tuomisto, Harri; Kekkonen, Laura; Wright, Jonathan; Bergmann, Uffe; et al.
Highlights: Three different thorium containing fuel types are test irradiated. Fuel temperatures, cladding elongation and rod pressures are monitored online. Addition of 7% thorium to the uranium matrix lowers fuel temperatures. Measurements also indicate lowered temperatures of thorium–plutonium MOX fuel. Abstract: Thorium based fuels are being tested in the Halden Research Reactor in Norway with the aim of producing the data necessary for licensing of these fuels in today's light water reactors. The fuel types currently under irradiation are thorium oxide fuel with plutonium as the fissile component, and uranium fuel with thorium as an additive for enhancement of thermo-mechanical and neutronic fuel properties. Fuel temperatures, rod pressures and dimensional changes are monitored on-line for quantification of thermo-mechanical behavior and fission gas release. Preliminary irradiation results show benefits in terms of lower fuel temperatures, mainly caused by improved thermal conductivity of the thorium fuels. In parallel with the irradiation, a manufacturing procedure for thorium–plutonium mixed oxide fuel is developed with the aim to manufacture industrially relevant high-quality fuel pellets for the next phase of the irradiation campaign.